Are there sensitive neighbourhood effect periods during the life course on midlife health and wellbeing?. (May 2019) - Jivraj, Stephen; Norman, Paul; Nicholas, Owen; Murray, Emily T.
Abstract: Since the turn of the century there has been an explosion in the number of epidemiological studies that have analysed neighbourhood effects on health and wellbeing. The vast majority of these studies are cross-sectional in nature and assume that a contemporaneous place of residence captures a meaningful neighbourhood effect. Over the same time frame, social epidemiology has focussed increasingly on life course effects. This paper aims to bring these two areas of study together and tests whether there a certain ages during the life course when neighbourhoods are more important for our health and wellbeing than others. We use two British birth cohort studies (1958 National Child Development Study and British Cohort Study 1970) each comprising approximately 6, 000 sample members at midlife linked to historic census measures used to derived Townsend neighbourhood deprivation scores over the life course. We find little evidence to support our hypothesis that adolescence is a key period of neighbourhood effect, rather we find late-early-adulthood neighbourhood deprivation and midlife neighbourhood deprivation are more strongly related to mid-life health and wellbeing. We are not able to conclude whether these effects are causal and encourage further investigation of selection mechanisms into neighbourhoods and mediation throughout the life course using our newly created dataset. Highlights: Contemporaneous neighbourhood deprivation is most strongly related to mid life health and wellbeing. There is evidence for sensitive periods of neighbourhood effects at or around age 30 on health and wellbeing at midlife. It is important to take neighbourhood deprivation across the life course to determine the total effect.